Descartes: entre la psicología racional y la antropología filosófica - Cebrecos Bravo, Fermín (2014)
The purpose of this study is to discuss the Cartesian relationship between rational psychology and philosophical anthropology which originates from the concept of substance. The ontological dualism between the two finite substances (res cogitans and res extensa) specifically introduced in the Metaphysical Meditations is significantly restricted in two further works, the Traité de l’homme and De passionibus animae, in which there is an explicit reference to the pineal gland as the physical contact between mind and body. In this sense, Descartes in his search for an explanation of the mind-body interaction from a physiological point of view promotes a middle ground between a rational psychology, which defines human nature solely as a soul, and a philosophical anthropology, which view human beings as a psychosomatic unity.